Corporate Social Responsibility (CSR) by small and medium enterprises (SMEs): a systematic review; Responsabilidad Social Corporativa (RSC) en las pequen\~as y medianas empresas (PYMEs): una revisioń sistemat́ica - Grace Bikefe; Umaru Zubairu; Simeon Araga; Faiza Maitala; Ekanem Ediuku; Daniel Anyebe (Small Business International Review (SBIR), 2020)
This study aims to systematically review the key characteristics and issues in Corporate Social Responsibility among Small and Medium Enterprises (CSRS) research. The Systematic Assessment Quantitative Technique (SQAT) developed by Australian researchers, Catherine Pickering and Jason Antony Byrne, was used to identify and analyse 62 peer-reviewed CSRS articles from six high quality academic databases. Most of the studies took place in Europe and Asia while South America has been largely ignored. A significant number of CSRS research were empirical in nature, meaning that there is a need for more conceptual studies to aid the understanding of new CSRS norms and underlying factors. Additionally, CSRS articles focused mainly on identifying the various ways SMEs are implementing CSR. Finally, most CSRS articles adopted a single research method, with survey being the most dominant method. There is a need for future studies to combine a variety of methods so as to gain additional insight into CSRS related issues. – – Este estudio tiene como objetivo revisar sistemat́icamente las caracteriśticas y los problemas claves en la investigacioń de la Responsabilidad Social Corporativa en las Pequen\~as y Medianas Empresas (RSC). Empleando la tećnica cuantitativa de evaluacioń sistemat́ica (SQAT), desarrollada por los investigadores australianos, Catherine Pickering y Jason Antony Byrne, se identificaron y analizaron 62 artićulos revisados por pares de seis bases de datos acadeḿicas de alta calidad. La mayoriá de los trabajos se realizaron en Europa y Asia, mientras que Ameŕica del Sur ha quedado ignorada en gran medida. Un nuḿero significativo de investigaciones fueron de naturaleza empiŕica, lo que significa que existe una necesidad de maś estudios conceptuales para ayudar a comprender las nuevas normas y los factores subyacentes sobre RSC. Ademaś, los artićulos de RSC se centraron principalmente en identificar las diversas formas en que las PYME estań implementando la RSC. Finalmente, la mayoriá de los artićulos adoptaron un uńico met́odo de investigacioń, siendo la encuesta el met́odo maś dominante. Es necesario que los estudios futuros combinen una variedad de met́odos para obtener informacioń adicional sobre los problemas relacionados con la RSC.
Keywords: M14; M15; 650; Corporate Social Responsibility; SMEs; systematic review; Responsabilidad Social Corporativa; PYMEs; revisioń sistemat́ica